Entrepreneurship as a career option: do temporary workers have the competencies, intention and willingness to become entrepreneurs? - Costa, S. F. (2016)
This study analyses the entrepreneurial intentions and the willingness of temporary workers to consider entrepreneurship as a career option. Specifically, we analyse the self-perception of entrepreneurial competencies of a group of temporary workers. A total of 184 temporary workers participated in the study. We performed a multiple correspondence analysis (MCA) to identify profiles of entrepreneurial competencies according to temporary workers' entrepreneurial intention and willingness to consider entrepreneurship as a career option. We conclude that temporary workers do not always perceive themselves as having the necessary competencies to choose for entrepreneurship in their occupational paths. The self-perception of different levels of entrepreneurial competencies is also associated with different intentions and willingness to consider entrepreneurship as a career option. Finally, we provide insights for practice, which can be considered as a starting point for activities aiming to develop entrepreneurial competencies at the individual or organisational levels.